3D composite particles - Maslovsky, Yu.N.; Slipushenko, S.V.; Tur, A.V.; Yanovsky, V.V. (Functional Materials, 2015)
The simple model of three-dimensional particle with internal degrees of freedom that interact with each other is proposed. The typical kinematic modes of motion of such particle with a small number of internal degrees of freedom are considered. Analytically investigated are all modes of motion of particle with one internal degree of freedom. We show that appearance of chaotic regimes is typical and found the mechanism of chaotization starting from two internal degrees of freedom. Obtained are the basic rules of motion of such particles and of the redistribution of energy of the internal degrees of freedom.